The social relevance of postgraduate management education: a case study of India - Vyakarnam, Shailendra (Cranfield University, 1987)
The study reported here, consists of three main parts. The first deals with the issue of the importance on management education in a poor country, some of the reported effects and therefore the question of relevance is raised. Proponents of the free market system argue that the only role of a manager is to make a profit for the business. However, in a country like India where the majority of the population is outside the mainstream of modern industrial life, there are arguments that freedom to make a profit should be accompanied by social responsibility because this form of behaviour helps to link modern industry with the wider social goals of a country. The second part of the study considers how to define and measure the social effects of publicly funded education. The outcome is the use of personal construct theory and repertory grid technique, borrowed from clinical psychology. which help to examine the social responsibility of Indian managers. The theory states that man makes choices and decisions based on the way he construes the world around him and the way he anticipates future events. The implication is that managers who construe social responsibility in terms of socio economic development are likely to make decisions which are more beneficial to society than those who have a narrower view of socially responsible behaviour. The third part of the study reports on the findings of the study, which has used five separate instruments with 53 Indian managers who have been trained at one of the three established Indian Institutes of Management. These Institutes (IIMs) train around 500 graduate managers each year and one of their objectives, is to "inculcate" social values in the graduates so that their future decisions as managers will be made in this context and be relevant to India's needs. The graduates are from among India's social elite and the way they construe social responsibility has been compared to a matched group of managers who have not been through the IIMs. Data has been collected, to classify the managers, on the social origins, their place of work and career orientations. The way they construe corporate and managerial social responsibility was elicited through the use of repertory grid technique, in order to examine the question of social responsibility in as many different ways as possible. Interestingly the results indicate insignificant differences between the two groups. These are interesting results as they highlight the possibility that the IIMs have not managed to instill socially responsible constructs which are any different from other Indian managers. Although this study is a snap-shot view of Indian managers, it does point to an area of research which the IIMs might take up, for example the objective of instilling social responsibility might not be achievable given all the other aims of the Institutions, or, if they feel that being of social consequence is important they might review their entry requirements, operational focus and so on. The main contribution of the results, to this issue, is a new approach to evaluating management education, helping to break from the conventional social cost benefit methods. This study has two further contributions of particular interest. First, it has examined social responsibility in a novel way and provided an empirically based definition. Secondly, the method used for this research has extended the application of personal construct theory to new areas of study, particularly by embodying repertory grid technique. There is little literature in construct theory which is of relevance to management education and this study has helped to close this gap.